Simplify: 25x(3/5

x + 4)

1 answer

The first step is to distribute the 25x to the terms inside the parentheses:

25x(3/5x + 4) = (25x)(3/5x) + (25x)(4)

Simplifying the first term:

(25x)(3/5x) = (25*3/5)(x*x) = 15x^2

Simplifying the second term:

(25x)(4) = 100x

Putting it all together:

25x(3/5x + 4) = 15x^2 + 100x
Similar Questions
  1. 1. Simplify 5^-1(3^-2)A. 45 B. 1/45 C. 15^-3 D. 15^2 2. Simplify (3xy^3)^2(xy)^6 A. 9x^8y^12 B. 3x^8y^12 C. 2x^3y^12 D. 9x^8y^9
    1. answers icon 7 answers
  2. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
more similar questions